RF and microwave transistor oscillator design - Grebennikov, Andrei (John Wiley, 2007)
This book presents up to date information on all aspects of oscillator design, enabling a selection of the best oscillator topologies with optimized noise reduction and electrical performance. RF and Microwave Transistor Oscillator Design covers: analyses of non-linear circuit design methods including spectral-domain analysis, time-domain analysis and the quasilinear method; information on noise in oscillators including chapters on varactor and oscillator frequency tuning, CMOS voltage-controlled oscillators and wideband voltage-controlled oscillators; information on the stability of oscillations, with discussions on the stability of multi-resonant circuits and the phase plane method; optimized design and circuit techniques, beginning with the empirical and analytic design approaches, moving on to the high-efficiency design technique; general operation and design principles of oscillators, including a section on the historical aspects of oscillator configurations.